Կոմիկական տարրերը Ք. Ամիսի «Հաջողակ Ջիմը» վեպում - Սյուզաննա Պողոսյան (ՀՀ ԳԱԱ հրատ.)
Kingsley Amis has written a marvelously funny novel describing the attempts of England's postwar generation to break lorn that country's traditional class structure. When it appeared in England, “Lucky Jim " provoked a heated controversy in which everyone took sides.
Keywords: Language and Literature